Predicting English Language Attainments in Higher Education: Self-efficacy Scales vs. Past Performances - Matthew Rudd Rudd (JETS: Journal of English Teaching Strategies, 2022)
This paper aims to empirically test Bandura’s (1977; 1986) claims that the beliefs people hold in their attainment potential predict standards of achievement more accurately than records of past performance, as the latter represent quiescent events unable to account for change. To investigate Bandura’s theoretical ideology, this quantitative research study thoroughly tested the accuracy of self-efficacy scales by comparing the grades 111 third-year university business students believed themselves capable of achieving vis-à-vis subsequent end-of-year English language scores. In relation to past performances, the present study compared students’previous second-year scores with those attained at the end of their current third year. This helped to determine whether students’ future performances can be computed more accurately as a function of their personal efficacy beliefs rather than by assumptions based on past performances. The results of this experiment were mixed. Initial t-test calculations inferred that there was no significant difference between prior stated beliefs of self-efficacy and end-of-third-year English scores (English Y3 = 63%; self-efficacy = 64.23%, p <0.05, not sig). In the same vein, students’ prior second-year scores were significantly different to those achieved in their third year (English Y3 = 63%; past performance Y2 = 56.64%, p <0.05, sig); suggesting that self-efficacy beliefs more reliably project future performances than past exploits. Nevertheless, while self-efficacy scales proved to be accurate in general terms, when measuring on a more task-specific level (such as speaking) or sub-group level (namely student ability), it transpired that such data deriving from self-efficacy scales became increasingly inconsistent. These confounding implications are discussed at length in this paper.